EFEKTIVITAS PENGENALAN AKAN KRISTUS DALAM PEMURIDAN SPK DI GEREJA MAHANAIM COMMUNITY CHURCH SEMARANG - Luhur, Chandra Kirana (Sekolah Tinggi Teologi Kristus Alfa Omega, 2019)
Many churches began to outreach through communal facilities in Semarang. This can be seen from the activity of the church in making discipleship for the members. From these circumstances, researchers feel interested to examine how effective the strategy of cell group leader in reaching new souls based on Act 2-4.To find out the effectiveness strategy of cell group leader to implementation in the outreach of the soul based on Act 2-4 in the Cell Groups?To know the most dominant dimension in the implementation of the effectiveness of the cell group leader in conducting the outreach by Act 2-4.To know the most influential background on the implementation of the effectiveness of the cell groupleaderÂ in conducting the outreach by Act 2-4.